2012
DOI: 10.1002/ece3.289
|View full text |Cite
|
Sign up to set email alerts
|

Environmental diel variation, parasite loads, and local population structuring of a mixed‐mating mangrove fish

Abstract: Genetic variation within populations depends on population size, spatial structuring, and environmental variation, but is also influenced by mating system. Mangroves are some of the most productive and threatened ecosystems on earth and harbor a large proportion of species with mixed-mating (self-fertilization and outcrossing). Understanding population structuring in mixed-mating species is critical for conserving and managing these complex ecosystems. Kryptolebias marmoratus is a unique mixed-mating vertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 93 publications
(116 reference statements)
4
34
0
Order By: Relevance
“…The other one, from Florida, USA, exhibited a bright orange coloration almost devoid of dark chromatophores, except the head. Ellison et al (2012) also found a male of K. marmoratus with orange coloration, faded ocellus and black borders on the anal and caudal fins in Belize; a pattern similar to that of the K. hermaphroditus male herein described.…”
Section: Discussionsupporting
confidence: 79%
“…The other one, from Florida, USA, exhibited a bright orange coloration almost devoid of dark chromatophores, except the head. Ellison et al (2012) also found a male of K. marmoratus with orange coloration, faded ocellus and black borders on the anal and caudal fins in Belize; a pattern similar to that of the K. hermaphroditus male herein described.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, males may play an important adaptive role in mixed-mating species where hermaphrodites can selffertilize but not outcross with other hermaphrodites. The environmental instability of the K. marmoratus habitat [64], widely different availability of males in different areas (less than 1% to greater than 20%) and the uniform distribution of isogenic lineages, without evidence of high local frequencies [65], suggest that reproductive assurance [66] may be the main adaptive advantage of selfing for K. marmoratus, as for other selfing species [65].…”
Section: Discussionmentioning
confidence: 99%
“…of MHC supertypes). INSTRUCT was run ten times for each value of K (1 -10) with a burn-in period of 10 000 replicates followed by 50 000 replicates to collect estimated parameters and likelihoods, as detailed in Ellison et al [67]. Fully homozygous individuals were excluded from this analysis as INSTRUCT is unable to estimate the number of selfing generations under total homozygosity.…”
Section: Methodsmentioning
confidence: 99%